PET Imaging for Dynamically Monitoring Neuroinflammation in APP/PS1 Mouse Model Using [18F]DPA714 - Hu, Wei; Pan, Donghui; Wang, Yalin; Bao, Weiqi; Zuo, Chuantao; Guan, Yihui; Hua, Fengchun; Yang, Min; Zhao, Jun (Frontiers in Neuroscience, 2020)
Background: In the pathogenesis of Alzheimer's disease (AD), microglia play an increasingly important role. Molecular imaging of neuroinflammatory targeting microglia activation and the high expression of 18-kDa translocator protein (TSPO) has become a hot topic of research in recent years. Dynamic monitoring neuroinflammation is crucial for discovering the best time point of anti-inflammatory therapy. Motivated by this, Positron emission tomography (PET) imaging in an APP/PS1 mouse model of AD, using 18F-labeled DPA-714 to monitor microglia activation and neuroinflammation, were performed in this paper. Methods: We prepared [18F]DPA714 and tested the biological characteristics of the molecular probe in normal mice. To obtain a higher radiochemical yield, we improved the [18F]-fluorination conditions in the precursor dosage, reaction temperature, and synthesis time. We performed [18F]DPA714 PET scanning on APP/PS1 mice at 6–7, 9–10, 12–13, and 15–16 months of age, respectively. The same experiments were conducted in Wild-type (Wt) mice as a control. Referring to the [18F]DPA714 concentrated situation in the brain, we performed blocking experiments with PK11195 (1 mg/kg) in 12–13-months-old APP/PS1 mice to confirm the specificity of [18F]DPA714 for TSPO in the APP/PS1 mice. Reconstructed brain PET images, fused with the Magnetic Resonance Imaging (MRI) template atlas, and the volumes of interests (VOIs) of the hippocampus and cortex were determined. The distribution of [18F]DPA714 in the brain tissues of 15–16-months-old APP/PS1 and Wt mice were studied by immunofluorescence staining. Results: Through the reaction of 18F, with 2 mg precursor dissolved in 300 ul acetonitrile at 105°C for 10 min, we obtained the optimal radiochemical yield of 42.3 ± 5.1% (non-decay correction). Quantitative analysis of brain PET images showed that the [18F]DPA714 uptake in the cortex and hippocampus of 12–13-months-old APP/PS1 mice was higher than that of the control mice of the same age (cortex/muscle: 2.77 ± 0.13 vs. 1.93 ± 0.32, p = 0.0014; hippocampus/muscle: 3.33 ± 0.10 vs. 2.10 ± 0.35, p = 0.0008). The same significant difference was found between 15- and 16-months-old APP/PS1 mice (cortex/muscle: 2.64 ± 0.14 vs. 1.86 ± 0.52, p=0.0159; hippocampus/muscle: 2.89 ± 0.53 vs. 1.77 ± 0.48, p = 0.0050). Immunofluorescence staining showed that the activation of microglia and the level of TSPO expression in the cortex and hippocampus of APP/PS1 mice were significantly higher than Wt mice. Conclusion: [18F]DPA714, a molecular probe for targeting TSPO, showed great potential in monitoring microglia activation and neuroinflammation, which can be helpful in discovering the best time point for anti-inflammatory therapy in AD.